1997
DOI: 10.1021/js970188t
|View full text |Cite
|
Sign up to set email alerts
|

Amlodipine Inhibits Rat Microsomal Cytochrome P450-Mediated Drug Biotransformation

Abstract: Calcium channel antagonists have been shown to inhibit cytochrome P-450-mediated metabolism both in vitro and in vivo. The purpose of the present study was to examine the effect of amlodipine on a suite of rat hepatic microsomal cytochrome P-450 activities to determine the potential for drug interactions. In this study, amlodipine (0.05 and 0.5 mM) decreased CYP1A-mediated ethoxyresorufin O-deethylase activity in microsomes prepared from noninduced (56 and 73% inhibition) and pyridine-induced (30 and 51% inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Amlodipine inhibited erythromycin N-demethylase activity in the rat liver microsomes [10], however, it appears unpublished whether CYP3A1/2 is involved in the metabolism of amlodipine in rats in vivo. Hence, rats were pretreated with troleandomycin, a main inhibitor of CYP3A1/2 in rats [16].…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Amlodipine inhibited erythromycin N-demethylase activity in the rat liver microsomes [10], however, it appears unpublished whether CYP3A1/2 is involved in the metabolism of amlodipine in rats in vivo. Hence, rats were pretreated with troleandomycin, a main inhibitor of CYP3A1/2 in rats [16].…”
Section: Resultsmentioning
confidence: 91%
“…Drobitch et al [10] reported that erythromycin N-demethylase (erythromycin is metabolized to N-demethylerythromycin via CYP3A2 in male rats [11]) activity was significantly inhibited by 1 mm amlodipine in both noninduced and induced rat liver microsomes. However, whether CYP3A1/2 is involved in the metabolism of amlodipine in rats in vivo seemed not to be reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, AML is often used in hypertensive patients after transplantation. Erythromycin is metabolized to Ndemethylerythromycin via CYP3A2 in male rats (Desjardins & Iversen, 1995) and the N-demethylase activity of erythromycin has been shown to be significantly inhibited by 1 mM AML in non-induced and induced rat liver microsomes, suggesting that CYP3A2 activity is inhibited by AML in rats (Drobitch et al, 1997). Human CYP3A4 is similar to rat CYP3A2 (Bogaards et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…AML is an inhibitor of CYP3A2 in rats (Drobitch et al, 1997) and a substrate of P-gp (Katoh et al, 2000;Kuzuya et al, 2003). Only one clinical case report (Leroy et al, 2010) has suggested that AML might increase the TAC concentration.…”
Section: Introductionmentioning
confidence: 99%